INFORMATION SYSTEM FOR A FUZZY COGNITIVE ANALYSIS AND MODELING - Gozhyi, Alexander; Kalinina, Irina (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper presents the information system for the cognitive analysis and modeling based on fuzzy cognitive map. The system allows to analyze the information of the experts to model complex systems and processes. Describes the structure of the system and the features of the functioning and implementation.